Trends in Israel's Medical Administration subspecialty, 1987–2022 - Yoel Angel; Hadar Goldshtein; Nevo Barel; Gil Fire; Michael Halberthal; Adi Niv-Yagoda (Israel Journal of Health Policy Research)
Abstract Background Israel is unique in offering a formal subspecialty in Medical Administration and mandating it for physicians applying for senior roles. Data on the prevalence and characteristics of these specialists are limited. Methods The national registry of licensed physicians was used to identify all living physicians who completed the Medical Administration subspecialty by December 31, 2022. Data on year of medical licensing, city of residence, and list of additional recognized specialties along with their respective date of completion were extracted. Websites of key public health organizations were sampled to identify qualifications of persons in senior leadership positions. Results Since 1987, 277 physicians have completed the Medical Administration subspecialty, with a significant increase in annual certifications from 4.5 in 2015 (interquartile range [IQR] 4–6) to 13 (IQR 10.5–15) in 2022 (p < 0.001). Specialists completed the subspecialty a median of 18 years (IQR 13–21) post-licensing, with 269 physicians (97.1%) holding additional specialties, primarily in Internal Medicine, Pediatrics, Family Medicine, or Public Health. Compared to the general physician population, some base specialties like Public Health are over-represented while others, like Anesthesiology, are under-represented. Only 40 (14.4%) specialists reside outside major metropolitan areas. Nineteen (61.3%) general hospital CEOs, 2 (20%) psychiatric hospital CEOs, 13 (35.1%) Ministry of Health and 4 (7.8%) Sick Fund executives are specialists in Medical Administration (p < 0.005). Conclusions The steady growth in the number of specialists in Medical Administration demonstrates the sustainability and scalability of this model, which may serve as a template for other healthcare systems. However, the limited representation of these specialists in senior roles of some organizations, and their concentration within certain specialties and regions, indicates areas for policy attention to enhance leadership diversity and reduce healthcare disparities.